Sb-AlxCy-C Nanocomposite Alloy Anodes for Lithium-Ion Batteries. (20th August 2016) - Hung, Nguyen Thanh; Park, Sung-Hoon; Bae, Joonwon; Yoon, Young Soo; Kim, Ji Hyeon; Son, Hyung Bin; Lee, Daeho; Kim, Il Tae; Hur, Jaehyun
Graphical abstract: We fabricated the high performances of Sb-Alx Cy -C nanocomposite alloy anodes using high-energy mechanical milling for use in lithium-ion batteries. Highlights: We fabricated Sb-Alx Cy -C nanocomposite alloy anodes by high-energy mechanical milling for use in lithium-ion batteries. The electrochemical performances, morphologies, and crystallographic features of AlSb and AlSbC with three different mixing ratios of Al and Sb were investigated. We found that AlSb(1:1)-C showed the best electrochemical performances in terms of specific capacity, cyclic performances, and rate capabilities. The mechanism of formation of AlSbC was examined by using XRD, TEM, and DCP data. Abstract: We present a facile approach to making Al-Sb, carbon-modified (Al-Sb-C) nanocomposites for use as new anode materials in lithium-ion batteries (LIB). Alloying is achieved by one step synthesis using high energy mechanical milling (HEMM), producing nanometer-sized alloy particles of Sb-Al x C y -C. Based on electrochemical analyses, we determined that Sb acts as an active material, and both Al and carbon create a hybrid buffering matrix that mitigates the volume expansion of the active material during lithiation/delithiation to a greater degree than that by a pure metallic matrix (AlSb). In addition, we optimized the stoichiometric ratio of Al and Sb with regard to specific capacity and cycling performance. Of the ratios tested, a 1:1 molar ratio of Al and Sb exhibited the best cycling performance (302.5 mAh g −1 after 200 charge/discharge cycles). Although our Al-Sb-C composite had low initial coulombic efficiency (∼59%), recovery to ∼ 97% occurred within three cycles, indicating that initial side reactions are quickly reduced over the course of cycling. AlSb-C anodes also showed good rate capability and volumetric capacity. Overall, the new AlSb-C composite is a promising candidate for use as negative electrodes in lithium-ion batteries, providing an alternative to commercially available graphite electrodes.